2013
DOI: 10.1007/s10646-013-1170-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic evaluation in Oreochromis niloticus (Fish: Characidae) of recombinant spore–crystal complexes Cry1Ia, Cry10Aa and Cry1Ba6 from Bacillus thuringiensis

Abstract: Bioinsecticides from Bacillus thuringiensis (Bt) are widely used around the world in biological control against larval stages of many insect species. Bt has been considered a biopesticide that is highly specific to different orders of insects, non-polluting and harmless to humans and other vertebrates, thus becoming a viable alternative for combating agricultural pests and insect vectors of diseases. The family of Bt δ-endotoxins are crystal-protein inclusions showing toxicity to insects' midgut, causing cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
(27 reference statements)
1
5
0
2
Order By: Relevance
“…When analyzing hematologic data from mice, not only concurrent controls should be used as the primary comparison for interpretation of treatment-related changes, but also comparisons with reference intervals, which are desirable to put hematologic changes in perspective [ 15 ]. Thus, this study has demonstrated that the levels of toxicity depend on the strain of spore-crystal and its exposure levels, as we have also shown in our previous study with these same spore-crystals [ 19 ]. Considering that more than 50 Cry proteins have already been well-characterized, and that their structure shows three domains responsible for forming pores in the membranes of the susceptible cells, causing lysis, variations in these domains could be responsible for the variations in toxicity because of their requirement to bind to specific receptors for activity [ 29 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…When analyzing hematologic data from mice, not only concurrent controls should be used as the primary comparison for interpretation of treatment-related changes, but also comparisons with reference intervals, which are desirable to put hematologic changes in perspective [ 15 ]. Thus, this study has demonstrated that the levels of toxicity depend on the strain of spore-crystal and its exposure levels, as we have also shown in our previous study with these same spore-crystals [ 19 ]. Considering that more than 50 Cry proteins have already been well-characterized, and that their structure shows three domains responsible for forming pores in the membranes of the susceptible cells, causing lysis, variations in these domains could be responsible for the variations in toxicity because of their requirement to bind to specific receptors for activity [ 29 ].…”
Section: Resultssupporting
confidence: 81%
“…Aquatic exposure of spore-crystals Cry1Aa, Cry1Ab, Cry1Ac e Cry2Aa to zebrafish at different exposure levels showed low toxicity and no genotoxicity, except for Cry1Aa which increased the micronucleus levels in peripheral erythrocyte cells [ 18 ]. In addition, in our previous study of Oreochromis niloticus exposed to Bt spore-crystals Cry1Ia, Cry10Aa and CyrBa6 for 96 h no mutagenicity was observed through micronucleus test or DNA damage by the comet assay in peripheral erythrocyte cells [ 19 ]. Additionally, mice orally treated with Bt spore-crystals genetically modified to express individually Cry1Aa, Cry1Ab, Cry1Ac or Cry2A showed no genotoxic effect [ 20 ], corroborating our results.…”
Section: Resultsmentioning
confidence: 99%
“…Non-target aquatic vertebrates can be exposed to Bt as a result of biological treatments aimed against insect pests or mosquitos. Most researchers report that Bt spores parasporal bodies are not toxic for fishes [ 152 , 154 , 155 , 156 , 157 ]. Snarski [ 157 ] observed no adverse effects of exposure of Bt var.…”
Section: Vertebratesmentioning
confidence: 99%
“…Moreover, upon the transfer to Bt -free water, fishes effectively excreted the toxins from their organisms [ 157 , 158 ]. No genotoxic or mutagenic effects of Bt toxins on peripheral erythrocyte cells of Oreochromis niloticus were observed [ 154 ]. Cry1Ba6 and Cry10Aa toxins did not show adverse effects to O .…”
Section: Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation